Strategy of Derivatives Hedging: Maintaining and Increasing Firm Value amidst Market Volatility in Indonesia: English - Purnomo, Heri; Sugeng, Bambang; Handayati, Puji (Shafin: Sharia Finance and Accounting Journal, 2024)
This study examines the relationship of derivative hedging and firm value. With 1520 observations from 380 Indonesian non-financial firms. The research method used is quantitative explanatory with regression analysis panel data. We involved eight control variables to adjust the influence of external factors. We found that the application of derivative hedging strategies contributes to an increase in the firm value through risk reduction. We also found that commodity derivatives and currency derivatives play a more active role as risk tools than interest rate derivatives. In the context of economic uncertainty and high market fluctuations, firms are exposed to various financial risks, including currency and commodity risks. By implementing an effective hedging strategy, the firm can reduce cash flow volatility and increase financial stability. In addition, reducing uncertainty through risk management can improve investor perception and lower the cost of capital. This result is in line with the principle of Modigliani & Miller (1958) that the firm value is determined by the resulting cash flow. Thus, the practice of risk management is not only relevant but can also reinforce the propositions of Modigliani & Miller (1958) in a more realistic and specific context. The findings underscore the importance of proactive risk management in the face of dynamic market challenges. In addition, this study provides new insights into hedging practices in developing countries. With a better understanding of the impact of using derivatives, firms can manage risk more efficiently and increase their attractiveness in the eyes of investors. So that firm managers can plan the use of derivative instruments as an effective hedging strategy.